Evaluation of pregnancy diagnosis using ultrasonography in goats - Azizunnesa, -; Reza, MMB; Parvez, MA; Faruk, MO (Bangladesh Veterinarian, 2019)
Pregnancy status in 250 goats was determined by transabdominal ultrasonography. The registered hospital cases were divided into groups A (mated naturally; 88); B (postpartum reported unmated; 112) and C (pubertal unmated; 50). Animals found to be non-pregnant and free of uterine infection were labelled Group D and divided into synchronized (S) and control (NS) groups. GnRH followed byPGF2α nine days later was injected i.m. in group S, and NS group were allowed natural mating. All mated goats were checked monthly for pregnancy using ultrasonography. Pregnancy was diagnosed in 45.5, 4.5 and 0% from naturally mated, postpartum reported unmated and pubertal unmated cases, respectively. The oestrus detection and pregnancy rates varied significantly (P<0.001) between synchronized (n = 96; 70.8 and 54.4%, respectively) and NS group (n = 96: 54.0 and 28.6%, respectively). Pregnancy rates significantly varied in different months in gestation (P<0.05). Fetal viability rate was low in 1st month of pregnancy compared to other months (2nd, 3rd and >3rd). The confirmation of expected date of delivery (EDD) was low in 1st month of gestation compared to other months. Transabdominal ultrasonographic scanning helps to confirm pregnancy in goats. From 2nd month of gestation ultrasound scanning confirms pregnancy with viable fetus (83.3%). At 3rd month of pregnancy, this technique determined the EDD up to 94.2%. The Bangladesh Veterinarian (2019) 36(1 - 2): 42-48